Fuel economy of multiple conditions self-adaptive tractors with hydro-mechanical CVT - Xiao, Maohua; Zhao, Jing; Wang, Yuewen; Zhang, Haijun; Lu, Zhixiong; Wei, Weihua (International Journal of Agricultural and Biological Engineering, 2018)
Fuel economy is one of the most important properties of wheeled tractors. To improve the fuel economy, it is necessary to improve the engine fuel economy and the tractive efficiency of the driving mechanism. By analyzing the fuel economy evaluation index of wheeled tractors, the correlation among the tractor specific fuel consumption, the engine effective specific fuel consumption and the tractive efficiency of the driving mechanism were clarified in this paper. A tractor with a new type of hydro-mechanical continuously variable transmission (HMCVT) was designed and its whole model was established too. On the basis of each module’s simulation model, the binary speed ratio matching simulation model of the gearbox-engine system was obtained by the control system reconstruction, and the fuel economy simulation analysis of the wheeled tractor with HMCVT was carried out under the two typical working conditions of plowing and sowing. Compared with the current national standard, the fuel economy of the newly designed wheeled tractors with the power of 130 kW was 380 g/(kW·h), specific fuel consumption was reduced by 21.1%. The results showed that the new tractor fuel economy was greatly improved. Further, automatic navigation technology can be combined with the self-adaptive tractors to adapt to different working conditions and achieve the optimal fuel economy, which can be applied in precision agriculture. Keywords: high power wheeled tractor, self-adaptive tractor, HMCVT, fuel economy, navigation DOI: 10.25165/j.ijabe.20181103.2158 Citation: Xiao M H, Zhao J, Wang Y W, Zhang H J, Lu Z X, Wei W H. Fuel economy of multiple conditions self-adaptive tractors with hydro-mechanical CVT. Int J Agric & Biol Eng, 2018; 11(3): 102–109.